Islamic State in Iraq and Syria (ISIS) and Its Impact in Indonesia - Tobing, Fredy B.L.; Indradjaja, Erwin (Global: Jurnal Politik Internasional, 2019)
This paper presents a historical and qualitative study to examine the rise of the Islamic State of Iraq and Syria (ISIS) as a force in international politics and its impacts on the dynamics of violent extremism threat in Indonesia. The rise of ISIS was a turning point from the nascent progressive shift toward democratization in the Arab world represented by the “Arab Spring,” and its influence has spread beyond Syria and Iraq to threaten regional and global security. Like in other countries in the Islamic world, Indonesian society and politics have been significantly affected by the activities of ISIS. In addition to describing the origin of ISIS and spread of its ideology, this paper examines the responses from Indonesian extremist and mainstream community to ISIS’ agenda. It argues that the conflicting responses primarily revolves around the notion of whether ISIS actually has qualities of a functional state. The role of moderate Islamic mass organisations such as Nahdlatul Ulama and Muhammadiyah has also proven to be important in resisting the spread of ISIS’ ideology in Indonesia.